Extracellular vesicles would be involved in the release and delivery of seminal TGF-β isoforms in pigs - Padilla, Lorena; Barranco, Isabel; Martínez-Hernández, Jesús; Parra, Ana; Parrilla, Inmaculada; Pastor, Luis Miguel; Rodriguez-Martinez, Heriberto; Lucas, Xiomara; Roca, Jordi (Frontiers in Veterinary Science, 2023)
Introduction Pig seminal plasma (SP) is rich in active forms of all three isoforms (1-3) of transforming growth factor β (TGF-β), a chemokine modulatory of the immune environment in the female genital tract once semen is delivered during mating or artificial insemination (AI). The present study aimed to examine how TGF-βs are secreted by the epithelium of the male reproductive tract and how they are transported in semen, emphasizing the interplay with seminal extracellular vesicles (sEVs). Methods Source of TGF-βs was examined by immunohistochemistry in testis, epididymis, and accessory sex glands, by immunocytochemistry in ejaculated spermatozoa, and by Luminex xMAP® technology in SP and sEVs retrieved from healthy, fertile male pigs used as breeders in AI programs. Results All three TGF-β isoforms were expressed in all reproductive tissues explored and would be released into ductal lumen either in soluble form or associated with sEVs. Ejaculated spermatozoa expressed all three TGF-β isoforms, both inside and outside, probably the outer one associated with membrane-bound sEVs. The results confirmed that pig SP contains all three TGF-β isoforms and demonstrated that a substantial portion of them is associated with sEVs. Discussion Seminal EVs would be involved in the cellular secretion of the active forms of seminal TGF-β isoforms and in their safe transport from the male to the female reproductive tract.